Axenfeld-Rieger Syndrome Associated with Congenital Glaucoma and Cytochrome P4501B1 Gene Mutations - Mukesh Tanwar; Tanuj Dada; Rima Dada (Case Reports in Medicine)
Developmental anomalies of the ocular anterior chamber angle may lead to an incomplete development of the structures that form the conventional aqueous outflow pathway. Thus, disorders that present with such dysfunction tend to be associated with glaucoma. Among them, Axenfeld-Rieger (ARS) malformation is a rare clinical entity with an estimated prevalence of one in every 200,000 individuals. The changes in eye morphogenesis in ARS are highly penetrant and are associated with 50% risk of development of glaucoma. Mutations in the cytochrome P4501B1 (CYP1B1) gene have been reported to be associated with primary congenital glaucoma and other forms of glaucoma and mutations in pituitary homeobox 2 (PITX2) gene have been identified in ARS in various studies. This case was negative for PITX2 mutations and compound heterozygote for CYP1B1 mutations. Clinical manifestations of this patient include bilateral elevated intraocular pressure (>40 mmHg) with increased corneal diameter (>14 mm) and corneal opacity. Patient also had iridocorneal adhesions, anteriorly displaced Schwalbe line, anterior insertion of iris, broad nasal bridge and protruding umbilicus. This is the first study from north India reporting CYP1B1 mutations in Axenfeld-Rieger syndrome with bilateral buphthalmos and early onset glaucoma. Result of this study supports the role of CYP1B1 as a causative gene in ASD disorders and its role in oculogenesis.